Determination of unacceptable HLA antigen mismatches in kidney transplant recipients: recommendations of the German Society for Immunogenetics. Issue 5 (November 2015) - Süsal, C.; Seidl, C.; Schönemann, C.; Heinemann, F. M.; Kauke, T.; Gombos, P.; Kelsch, R.; Arns, W.; Bauerfeind, U.; Hallensleben, M.; Hauser, I. A.; Einecke, G.; et al.
Abstract One of the major tasks of histocompatibility and immunogenetics laboratories is the pretransplant determination of unacceptable antigen mismatches (UAM) in kidney transplant recipients. In this procedure, human leucocyte antigen (HLA) specificities are defined against which the patient has circulating alloantibodies that are expected to harm the transplanted organ. Using the information on UAM and the potential donor's complete HLA typing, prediction of the crossmatch result, the so called 'virtual crossmatch', is possible. Currently, the laboratories are using different algorithms for the determination of UAM, and depending on the algorithm, more or fewer organ offers are excluded for patients with a similar antibody profile. In order to bring homogeneity into the allocation of organs to immunized patients in Germany, the German Society for Immunogenetics established, on the basis of current knowledge, recommendations for the determination of UAM. The UAM recommendations, which are thought to serve as a common tool for responsible physicians at different transplant centers, contain technical issues that need to be considered and are individualized for sensitized patients with a high or intermediate risk of antibody‐mediated rejection. The present review contains these recommendations and puts them into perspective to current international practice.